Perlindungan Hukum Privasi Dan Data Pribadi Konsumen Pengguna Jasa Aplikasi Grab - Ira Yanti; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2023)
This study aims to analyze the regulation of personal data and legal protection of consumer personal data for misuse of personal data and efforts that can be made by consumers of online transportation services against misuse of consumer personal data with case studies ordering food from the grabfood application. This research uses internet searching method, interview searching and library research approach. Where this internet searching method is the process of searching data through internet media to obtain information based on references, journals, articles and legislation online relating to the object of research. In addition, internet searching is also interpreted as searching data using the internet in order to find supporting data needed for research. Internet searching is also known as online search method. The way to do this is through data tracking, through online media so that it allows researchers to utilize information data in the form of data or theory which if it can help to conduct research. Then the searching interview or interview is a conversation between two people to get some information that is useful for research. Interviews were conducted in this study by sharing several questions via social media with several research objects and finally the library research approach, namely conducting research from various library sources, including books, journals, magazines, newspapers, and documents used to search for objects. which are desired. Regulations for personal data protection in Indonesia are still regulated in several sectoral arrangements. Use of personal data without the consent of the owner of personal data, including misuse of personal data. In the terms of use of the grab service, consumer personal data settings are regulated in the grab privacy policy. The grab application protects grab users' personal data from data leaks and is used by other parties without the consent of the data owner. Meanwhile, the form of legal protection of personal data against misuse of personal data can be subject to sanctions in the form of imprisonment or administrative sanctions. There needs to be a comprehensive regulation that specifically regulates the protection of consumer personal data. Consumers can resolve disputes by deliberation, arbitration and court.